PENGARUH KONSENTRASI BIOURINE SAPI TERHADAP PERTUMBUHAN DAN HASIL TANAMAN SAWI HIJAU (Brassica juncea L) - Oyan Rusdianto Edwin Ole Awa; Putu Eka Pasmidi Ariati; Farida Hanum; Ramdhoani; Luh Putu Yuni Widyastuti (Faculty of Agriculture and Business, Universitas Mahasaraswati Denpasar , Kec. Denpasar Utara, Kota Denpasar, Bali 80233, 2023)
This study aims to determine the effect of cow biourine liquid fertilizer on the growth and yield of mustard greens. This research has been conducted on Jln. Banteng Baru behind the PDIP office No.4, Renon Village, South Denpasar District. Denpasar City. This study took place for 1 month 2 weeks from the time of seedling, starting on 19 February – 26 March 2021. This study used a randomized block design (RAK) with the treatment of liquid fertilizer consisting of 6 treatments and 4 replications, while the treatment was cow biourine. , so that 24 experimental units can be obtained. Concentration of cow biourine: K0= control, K1=100ml cow biourine/900ml water, K2=200ml cow biourine/800ml water, K3=300ml cow biourine/700ml water, K4=400ml cow biourine/600ml water, K5=500ml cow biourine /500ml of water. The results showed that the concentration of bovine biourine was given to mustard greens. The results showed that K4 treatment (400ml cow biourine/600ml water) on the growth parameters of mustard greens had a very significant effect on plant height, leaf area, total plant fresh weight, total oven dry weight of plants and only had a significant effect on leaf number. The concentration of cow biourine liquid fertilizer from 400ml cow biourine/600ml water resulted in the best growth of mustard greens, namely total plant fresh weight: 137.5 g and total plant oven dry weight: 18.40 g.